A randomized controlled trial of online acceptance and commitment therapy to improve diet and physical activity among adults who are overweight/obese. Issue 6 (8th December 2020) - Levin, Michael E; Petersen, Julie M; Durward, Carrie; Bingeman, Brittany; Davis, Elizabeth; Nelson, Cindy; Cromwell, Shannon
Abstract: Acceptance and commitment therapy (ACT) has shown benefit for improving diet, physical activity, and weight among adults who are overweight and obese. However, research to-date in this area has primarily evaluated ACT delivered through in-person interventions, which has more limited access relative to online formats. The present study evaluated an online guided self-help program that integrated ACT with nutrition education to improve healthy eating and physical activity. A sample of 79 adults who were overweight/obese was randomized to receive the 8-week ACT on Health program plus weekly phone coaching or to a waitlist. Participants completed 5.5 ACT sessions on average (out of 8) and reported moderately high program satisfaction. Participants in the ACT condition improved significantly more than the waitlist at posttreatment on the primary outcome of healthy eating index (HEI; based on 24-hr recall assessments) and almost all secondary outcomes assessing self-reported eating behaviors, weight, mental health, weight self-stigma, and psychological inflexibility. However, no intervention effects were found for self-reported physical activity. At 8-week follow-up, improvements were maintained for most outcomes in the ACT condition, but not for the HEI. Improvements in psychological inflexibility mediated treatment effects on some outcomes, but not HEI or weight. Overall, delivering ACT through online guided self-help combined with nutrition education appears promising for improving healthy eating, weight, and self-stigma, but results for physical activity and long-term behavior change are unclear, possibly due to limitations in the ACT on Health program.